2021
DOI: 10.1088/1742-6596/1848/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Application of Children’s Reading Analysis Based on Artificial Intelligence——Take Small “raccoon Reading” and “Jiao Jiao Reading” as examples

Abstract: Artificial intelligence technology is widely used in the field of education, and the development of children’s Chinese reading field is increasingly mature. Using the boundary awareness of AI algorithm for reference, the Chinese reading class should also awaken the boundary awareness of Chinese subject. In the AI algorithm, only the annotated data are valid data. The reading text can become effective learning materials through natural language processing only when it is “annotated” out of ability points. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Considering that technology brings motivation and efficiency to education (Temizyürek & Ünlü, 2015), it is thought that the use of applications blended with technology in language teaching will contribute even more to the process. In most of the studies conducted today, it has been determined that AI applications contribute positively to the development of students' language and literacy skills (Ai, 2017;Broda & Frank, 2015;Divekar et al, 2022;Dizon, 2020;Nini & Kong, 2021;Rad et al, 2023;Utami et al, 2023). In their systematic literature review, Woo and Choi (20021 also found that artificial intelligence applications developed for four basic language skills, pronunciation, grammar and vocabulary had a positive impact on students' language skills.…”
Section: Artificial Intelligence In Language Educationmentioning
confidence: 99%
“…Considering that technology brings motivation and efficiency to education (Temizyürek & Ünlü, 2015), it is thought that the use of applications blended with technology in language teaching will contribute even more to the process. In most of the studies conducted today, it has been determined that AI applications contribute positively to the development of students' language and literacy skills (Ai, 2017;Broda & Frank, 2015;Divekar et al, 2022;Dizon, 2020;Nini & Kong, 2021;Rad et al, 2023;Utami et al, 2023). In their systematic literature review, Woo and Choi (20021 also found that artificial intelligence applications developed for four basic language skills, pronunciation, grammar and vocabulary had a positive impact on students' language skills.…”
Section: Artificial Intelligence In Language Educationmentioning
confidence: 99%
“…Therefore, in the traditional service model in the past, a certain emotional factor was introduced to allow users to experience the inner scene while enjoying ordinary services, which not only attracts the interest of more readers but also makes readers more engaged with the content. A deep understanding of the content will favour such a service model (Huang & Kong, 2021). For example, in recent years, many industries have developed service models with contextualization as the basic concept, such as contextualized games, and contextualized tourism .…”
Section: Introduction the Application Of Micro-video Technology In Th...mentioning
confidence: 99%